Artist and Patron in Postwar Japan : Dance, Music, Theater, and the Visual Arts, 1955-1980 - Havens, Thomas R. H. (Book collections on Project MUSE., 1982)
This work explains how and why Japan supports a community of professional dancers, musicians, production companies, and visual artists that has nearly tripled in size during the past 25 years. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.